KOMUNITAS ARAB: KONTINUITAS DAN PERUBAHANNYA DI KOTA SURABAYA 1900–1942 - Rabani, La Ode; Artono, Artono (P2KK LIPI, 2005)
This article was aimed to explanation of the continuity and change Arab communities in Surabaya cities 1900 – 1942. The development included the community life since the migration to Surabaya, social, politic, economic, and other following effects. This study found mort Arabs who came to Surabaya were from Hadramaut, the infertile highland. When the Suez Canal was opened In 1869, the Arabs migrated to Netherlands East Indies, especially to Surabaya. The Arabs migration came from Al Makalla (Asy Syihr) path to Bombay, Ceylon, Singapore, and Aceh. From Aceh and Singapore, the Arab went to different areas in Indonesia like Batavia, Cirebon, Tegal, Pekalongan, and Surabaya. The local people respected the Arabs, because of their efforts in spreading Islam, especially wali and kiai. That position gave benefits for Arabs because they were accepted in society easily, eventhough some of then were renters. This profession was absolutely forbidden and prohibited in Islam. In this context, it could be seen that religion was not always in accordance with economy activities indeed, religion was the media for economy activities. Key Word: migration, society, network, and change